2014
DOI: 10.1093/ejcts/ezu310
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional printing in cardiac surgery and interventional cardiology: a single-centre experience

Abstract: The fabrication of 3D printing models is feasible for perioperative planning and simulation in a variety of complex cases in paediatric and adult cardiac surgery, as well as in interventional cardiology. Further studies including more patients and providing more data are expected to demonstrate that the use of 3D printing may decrease morbidity and mortality of complex, non-routine procedures in cardiovascular medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
146
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(151 citation statements)
references
References 21 publications
0
146
0
5
Order By: Relevance
“…3D printing is more cost-effective for challenging cases rather than routine cases. The cost and time of manufacturing a 3D model vary between $100-450 and 30 min-107 h, respectively, depending on the size and materials of the model [12,18,37]. To print a 3D model, a cardiologist has to buy at least a 3D printer and the raw materials.…”
Section: How Can We Make a Cost-effective Analysis Before Printing A mentioning
confidence: 99%
“…3D printing is more cost-effective for challenging cases rather than routine cases. The cost and time of manufacturing a 3D model vary between $100-450 and 30 min-107 h, respectively, depending on the size and materials of the model [12,18,37]. To print a 3D model, a cardiologist has to buy at least a 3D printer and the raw materials.…”
Section: How Can We Make a Cost-effective Analysis Before Printing A mentioning
confidence: 99%
“…Two years later, Kim et al [9] employed 3DP models in the preoperative evaluation of ventricular septal defect, atrial septal defect, artificial mitral valve perivalvular leakage, and thoracic aortic pseudoaneurysm. In 2015, they reviewed their single-center experience using 3DP for preoperative evaluation and concluded that 3DP could reduce the mortality and morbidity of complicated cardiac surgeries [10]. None of these preliminary studies, however, have focused on the application of 3DP to ASD with insufficient defect rim near major blood vessels, including IVC, SVC, and aorta.…”
Section: Discussionmentioning
confidence: 99%
“…When an operation is not successful, 3Dp models can be created postmortem in order to analyse whether the correct interventional choices were made. A patient's 'porcelain aorta' has been printed after a transcatheter aortic valve implantation (TAVI) procedure resulted in an ischaemic event and death, and allowed identification of abnormal anatomy that was incompatible with the normal valve deployment site (Schmauss et al, 2015).…”
Section: D-printing In Intra-operative Guidancementioning
confidence: 99%
“…With development and innovation of the technology driving down costs, the use of 3Dp has become more widespread, eventually resulting in United States Food and Drug Administration approval for several 3Dp devices (Lee, 2016). As described above, 3Dp has many advantages for surgical usage and has become particularly popular in orthopaedic, maxillofacial, cranial and spinal surgery (Guenette et al, 2016;Liew et al, 2015;Onerci Altunay et al, 2016;Schwam et al, 2016;Tack et al, 2016;Wiedermann, et al, 2017;Xiao et al, 2016;Yang et al, 2016), whilst a growing number of case studies have described its use in fields such as interventional radiology (Ghisiawan, et al, 2017;Hossien et al, 2016;Kurup et al, 2015;Schmauss et al, 2015;Shi, et al, 2015;Sodian et al, 2009), paediatric surgery (Morrison et al, 2015;Schmauss et al, 2015) and oncological surgery (Al Jabbari et al, 2016;Bernhard et al, 2016;Matsumoto et al, 2016). To date, 3Dp models have been used primarily as surgical guides and for pre-operative surgical planning (Tack et al, 2016).…”
Section: Medical Usagementioning
confidence: 99%